Odpowiedzi

2010-02-14T01:29:59+01:00
A)
(5x+2)²=20x
25x²+20x+4=20x
25x²+20x-20x+4=0
25x²=-4 /:25
x²=-4/25--sprzeczne ponieważ jakaś liczba podniesiona do kwadratu nie może byc ujemna

b)
(1-3x)²=1-6x
1-6x+9x²=1-6x
9x²-6x+6x+1-1=0
9x²=0 /:9
x²=0
x=0

c)
(3+2x)²= (3x+2)²+10
9+12x+4x²=9x²+12x+4+10
4x²-9x²+12x-12x=4+10-9
-5x²=5 /:(-5)
x²=-1--sprzeczne ponieważ jakaś liczba podniesiona do kwadratu nie może byc ujemna

d)
x+9=(x-3)²
x+9=x²-6x+9
-x²+x+6x=9-9
-x²+7x=0
x(-x+7)=0
x=0 i -x+7=0
-x=-7 /:(-1)
x=7

e)
(4x-6)²=(x-4)(x-9)
16x²-48x+36=x²-9x-4x+36
16x²-x²-48x+13x=36-36
15x²-35x=0
5x(3x-7)=0
5x=0 /:5 i 3x-7=0
x=0 3x=7 /:3
x=7/3